Fresh, mechanical and microstructural properties of alkali-activated composites incorporating nanomaterials: A comprehensive review - Zhang, Chunwei; Khorshidi, Hossein; Najafi, Elham; Ghasemi, Marziyeh (Journal of cleaner production, 2023)
Nanomaterials possess outstanding physical, chemical, and electrical properties that differentiate them from conventional materials. Recently, nano-modified alkali-activated composites (AACs) or geopolymers have attracted attention owing to their excellent performance and modification mechanisms. This review paper encapsulates nano-modified AACs' fresh, mechanical, and microstructural properties. Nano-SiO2 was the most frequently used nanomaterial, accounting for 44% of the studies conducted. Regarding the types of composites, 55%, 29%, and 16% of the studies were focused on paste, mortar, and concrete, respectively. Most studies have shown that increasing the nanomaterials content in an alkaline medium reduced AACs consistency and setting time due to the small particle size, high specific surface area, unsaturated bonds, and high reactivity of nanomaterials. The results mostly indicated that while increasing nano-additives proportion to a certain extent improves the mechanical characteristics, including compressive, flexural, tensile, and impact strengths, incorporation beyond that amount deteriorates them. In terms of microstructure: porosity or homogeneity, amorphicity or crystallinity, and chemical bond variations have been investigated through analytical tests (SEM, XRD, and FTIR). The majority of performed studies acknowledged that incorporating nanomaterials brings about a denser, homogenous structure with more stable chemical bonds and a higher degree of amorphicity. This study has shown that provided that the precursor type and ultimate applicability of purposed building material were considered during the selection of type, amount, and mixing method of nanomaterials, their incorporation in AACs could have incredible effects on mechanical and microstructural properties of them and will facilitate fostering sustainable construction materials. •A comprehensive overview on the application of nanomaterials for the improvement of alkali-activated binder, mortar, and concrete.•A thorough investigation of fresh, mechanical, and microstructural properties of nano-modified AACs.•Determination of optimum nanomaterials content regarding the different properties.•A denser, homogenous structure, with more stable chemical bonds and a higher degree of amorphicity after nano-modification.